Self- awareness of consumers and their attitude to advertising - Ślaski, Sławomir; Jachnis, Anna; Strus, Włodzimierz (Studia Psychologica: Theoria et praxis, 2007)
The authors of the paper analyse a problem of impact of self-awareness on perception of advertisement. The theory of self-awareness elaborated by Zaborowski was the theoretical foundation of the research. It was hypothesized that the forms of self- awareness (i.e. outer, defensive, individual and reflective) should modify perception of the indirect advertisement (fliers). The hypotheses were partially confirmed. The outer and defensive forms of selfawareness influence on consumers’ perception of the advertisements. Further investigation are recommended.